2009
DOI: 10.1095/biolreprod.108.073395
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Fatherhood in Mice Decreases Reproductive Fitness and Longevity of Offspring1

Abstract: This study aims to analyze, in mice, the long-term effects of delayed fatherhood on reproductive fitness and longevity of offspring. Hybrid parental-generation (F(0)) males, at the age of 12, 70, 100, and 120 wk, were individually housed with a randomly selected 12-wk-old hybrid female. The reproductive fitness of first-generation (F(1)) females was tested from the age of 25 wk until the end of their reproductive life. In F(1) males, the testing period ranged from the age of 52 wk until death. Breeding F(1) fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Animal studies suggest that advanced parental age may reduce reproductive fitness and fecundity in female offspring (Tarin et al, 2003;Garcia-Palomares et al, 2009). These findings suggest that there may be a moderate association between parental age and timing of menarche as well.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Animal studies suggest that advanced parental age may reduce reproductive fitness and fecundity in female offspring (Tarin et al, 2003;Garcia-Palomares et al, 2009). These findings suggest that there may be a moderate association between parental age and timing of menarche as well.…”
Section: Discussionmentioning
confidence: 97%
“…Advanced maternal age at childbirth has been linked to menstrual disorders and subfecundity in daughters owing to endocrinological irregularities (Smits et al, 1997). Studies on mice have shown that delayed parenthood, both maternal and paternal, reduces reproductive fitness, particularly among female offspring (Tarin et al, 2003;Garcia-Palomares et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, and contrary to traditional belief, research has emerged to show that general paternal effects can affect a number of life-history traits in the offspring [4,6], and that these effects may also be sensitive to age-related senescence in fathers [6]. For example, studies have associated older fathers with the frequency of birth defects in humans [57], with reduced reproduction and longevity in laboratory mice (Mus musculus) [58], and with reduced fertility, offspring weight and increased offspring mortality in brown Norway rats (Rattus norvegicus) [59]. Paternal age effects have also been recorded in insects; old fathers have been noted to produce longer-lived offspring in D. melanogaster [52], and older fathers exhibited lower reproductive output when exposed to metabolic stress in the butterfly Pieris brassicae [20].…”
Section: Discussionmentioning
confidence: 99%
“…This has been examined particularly for the female gametes, or developing embryo (34,38,39), with relatively few examples of paternal programming. However, delaying fatherhood (40)(41)(42)(43), paternal smoking (44,45), and paternal alcohol consumption (46,47) have all been linked to impaired offspring health and longevity. There is some evidence that parental obesity increases the risk of children becoming overweight or obese (48,49), and similarly our initial preliminary observations in the mouse suggest that offspring from obese fathers were heavier before weaning than those from lean fathers.…”
Section: Discussionmentioning
confidence: 99%